Heritability of bud density and branching habit in almond - Sarvisé R.; Socias i Company R. (XIII GREMPA Meeting on Almonds and Pistachios, 2005)
The variability and heritability of bud location and distribution were studied in 14 families of the Zaragoza almond breeding programme involving 17 different parents. The traits studied included bud density, bud productivity, branching index, set and growing habit. Heritabilities by variance were more reliable than those from regression, probably due to the different growing conditions of the parents and the seedlings. Their values, however, were low, being 0.30 for bud density and 0.26 for bud productivity, probably related to the young age of the seedlings. Heritability was also low for branching index (0.19) and very low for fruit set (0.05), probably as a consequence of the great influence of the weather conditions on fruit set. Growth habit was very similar for all seedlings. The low heritabilities observed in these families could be due to the degree of closeness for these traits among the parents involved in these 14 progenies.
13. Meeting of the Mediterranean Research Group for Almond and Pistachio, 2003/06/01-05, Mirandela (Portugal)